When is the best time to use rubrics in flipped learning? A study on students' learning achievement, metacognitive awareness, and cognitive load. Issue 8 (17th November 2019) - Zhang, Yi; Chen, Bei-Lei; Ge, Jun; Hung, Cheng-Yu; Mei, Lin
ABSTRACT: Rubrics can guide teachers to provide effective feedback and students' peer- and self-assessment. This paper examines the effect of rubric use in flipped learning activities on students' learning achievement, metacognitive awareness, and cognitive load through a quasi-experiment. A total of 83 university students were randomly assigned to an experimental group or a control group. The students in the experimental group were given rubrics in performing pre-class learning activities on the cloud platform, while those in the control group used rubrics in post-class assessment and modification of their finished works. The results show that rubric use can assist flipped learning by improving students' learning achievement and metacognitive awareness, while reducing their cognitive load. Using rubrics before in-class work can yield stronger benefits in raising metacognitive awareness and lessening cognitive load. Moreover, the study reveals that students tend to hold a generally favorable attitude toward rubric use. These findings imply that appropriate use of rubrics in flipped learning has the potential to create a more efficient and learner-friendly condition to enhance self-regulated learning.